Revisiting symbolic interaction in music studies and new interpretive works - Denzin, Norman K. (Studies in symbolic interaction,, 2014)
Addressing a perceived gap between symbolic interaction and ethnomusicological approaches to the study of music, this special issue seeks to bring the fields closer by highlighting some of the complementary theoretical constructs of phenomenology and symbolic interaction as they relate to music studies.